2022
DOI: 10.1177/03057356221076177
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between musical behaviors and emotional states, humor styles, and coping humor

Abstract: Learning and performing music affect the brain and cognition and have a positive impact on emotional states. Negative emotional states such as stress, anxiety, and depression are harmful for teaching. Alternative certification teachers in particular are extremely vulnerable to and suffer greatly from negative emotional states. In addition, humor and coping humor are cognitive processes depending on neural networks of the brain. Therefore, the relationships between alternative certification pre-service teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…Negative emotions and cognitive load induced by participating in online learning environments and digital writing may be managed by affectively stimulating the learner by use of other educational technologies (Chen & Chang, 2009;Nazari et al, 2021). Remarkably, listening to music, is not only a useful educational tool for positively influencing cognition, emotional states, creativity, and coping skills (Burak et al, 2022;Cornett, 2007;Dulabaum, 2003;Flohr, 2006) but also is a powerful affective stimulus effecting persistence and volition in cognitively demanding digital tasks (Gendolla et al, 2021). Moreno and Woodruff (2021) reported that even background music is an effective affective stimulus on cognitive tasks and emotional states.…”
Section: Introductionmentioning
confidence: 99%
“…Negative emotions and cognitive load induced by participating in online learning environments and digital writing may be managed by affectively stimulating the learner by use of other educational technologies (Chen & Chang, 2009;Nazari et al, 2021). Remarkably, listening to music, is not only a useful educational tool for positively influencing cognition, emotional states, creativity, and coping skills (Burak et al, 2022;Cornett, 2007;Dulabaum, 2003;Flohr, 2006) but also is a powerful affective stimulus effecting persistence and volition in cognitively demanding digital tasks (Gendolla et al, 2021). Moreno and Woodruff (2021) reported that even background music is an effective affective stimulus on cognitive tasks and emotional states.…”
Section: Introductionmentioning
confidence: 99%